Description of Mother's Knowledge About the Growth and Development of Toddlers Ages 1-5 Years at the Village Maternity Cottage - Ismawati Ismawati; Hernah Riana; Hasliana Haslan (Newinera Publisher, 2020)
The purpose of this study was to describe the knowledge of mothers about the growth and development of toddlers aged 1-5 years at the village polindes (Village Maternity Cottage). Huko-Huko Village, Kec. Pomalaa. This type of research is descriptive with a population of 227. The sample of this study is the number of mothers who have children aged 1-5 years in Huko-huko Village in 2019, namely as many as 69. In determining the number of samples, the technique used is purposive sampling. This uses data obtained through a questionnaire. The results showed the level of knowledge about the growth and development of toddlers aged 1-5 years in Huko-huko Village in 2019 most of them had good knowledge as many as 37 people (53.62%) this shows the level of knowledge about the growth and development of toddlers aged 1-5 years in the village The shophouses of 2019 are well-informed. The government and health cadres must always be able to provide counseling to mothers of toddlers regarding infant growth and development.